Opening Access to Digital Collections: The State of Cultural Materials in Indonesian Higher Education Institutions - Putranto, Widiatmoko Adi (Springer Science and Business Media Deutschland GmbH, 2022)
This paper discusses the issue of opening access to digitized cultural heritage materials by examining the current state of their digital collections at the Indonesian higher education (HE) institutions in terms of their accessibility to the users. The accessibility is based on the online presence of the university libraries and the ability of the websites to provide sufficient information about the cultural heritage collections from the perspectives of the users. Eight Indonesian HE institutions with cultural heritage collections were identified. However, they have not been able to provide sufficient or explicit information on the cultural heritage collections online, including information on what collections are available, the basic descriptions of the items, and what users can do with the material. Therefore, raising awareness among Indonesian HE institutions, particularly the libraries, on the importance of opening access to cultural heritage collections is required.